Method of applying an optical security coating to a substrate - ZADJMAN DANIEL LIEBERMAN; PEREZ-SALAZAR RAMON BAUTISTA (2002)
This invention describes a removable optical security film of a type which includes a substrate with printed information and a first film which avoids the permanent adhesion of the optical security film to the substrate, whereby said optical film includes the temporary application of a removable material with adhesive characteristics on the substrate on which it is applied, and the engraving of optical elements on said removable material. In addition to authenticating the information printed underneath and avoiding the reprocessing of objects and prints, the optical security film also prevents the duplication of these objects and prints by conventional methods. In another embodiment of this invention, when the optical security film acts partially, the print and the non-removed parts of the film are the elements that authenticate the corresponding information.